Long-term efficacy of lobectomy for stage T1 papillary thyroid carcinoma with varying degrees of lymph node metastasis - Qin, Chao; Cai, Sijia; Qi, Yanyu; Liu, Meilin; Xu, Weibo; Yin, Min; Tang, Haitao; Ji, Qinghai; Liao, Tian; Wang, Yu (Frontiers in Endocrinology, 2024)
Background The presence of lymph node metastasis (LNM) is frequently observed in papillary thyroid carcinoma (PTC), and most clinical guidelines recommend total thyroidectomy. However, the impact of LNM on specific types of locoregional recurrence remains uncertain, particularly for stage T1 PTC. Methods The present retrospective cohort study enrolled patients diagnosed with stage T1 PTC between 2008 and 2015. Propensity score matching was performed in patients with lobectomy accompanied by varying degrees of LNM. Logistic regression analysis was performed to compare the effect of LNM on relapse types, and Kaplan-Meier method was utilized to calculate recurrence-free survival. Results The study cohort comprised 2,785 patients who were followed up for an average duration of 69 months. After controlling follow-up time and potential prognostic factors, we include a total of 362 patients in each group. Recurrence rates in the N0, N1a, and N1b groups were found to be 2.5%, 9.7%, and 10.2% respectively. Notably, group N1a versus group N0 (P=0.803), N1b group versus N0 group (P=0.465), and group N1b versus group N1a (P=0.344) had no difference in residual thyroid recurrence. However, when considering lymph node recurrence, both N1a(P=0.003) and N1b(P=0.009) groups showed a higher risk than N0 group. In addition, there was no difference in lymph node recurrence between N1b group and N1a group (P=0.364), but positive lymph node (PLN) and lymph node positive rate (LNPR) demonstrated a strong discriminatory effect (P<0.001). Conclusion Lobectomy may be more appropriate for patients with unilateral stage T1 PTC in the low LNPR group.